An Empirical Study of the Determinants of Sovereign Ratings : Evidence in ASEAN-5 Countries - Kurmanbayev, Saken (2013)
The research was carried out to analyze the determinants of the sovereign credit ratings provided by the two prominent rating agencies: Standard and Poor’s and Fitch Rating. Credit rating agencies have in recent literature been found to base their sovereign ratings on the same range of macroeconomic fundamentals. The purpose of this study is to find out whether these credit rating determinants are valid predictors when explaining actual defaults and not only affects the perceived creditworthiness of sovereigns. By studying a sample of five sovereign issuers in OLS approach, Logistic framework and Panel data this thesis finds that GDP per capita, GDP growth, current account to GDP and external debt works as determinants for actual sovereign defaults in addition to their role in determining credit ratings. The impact of the individual variables on the risk of default is also found to be in line with what is expected from earlier research and economic intuition.